Akten zur Auswärtigen Politik der Bundesrepublik Deutschland 1983 - Geiger, Tim (De Gruyter, 2014)
1983 was one of the tensest years of the Cold War. This volume publishes 389 documents for the first time that reveal West Germany`s efforts to maintain East-West dialogue in the face of intensified confrontation between the two blocs and to prevent collapse of the process of European unification. Among the successes were the decision for a follow-up CSCE conference in Madrid and the continuation of the special relationship with the East Germany.